The Role of Interpersonal Communication Among Health Cadres in Stunting Prevention: A Qualitative Analysis in East Jakarta - Novia Nuraini Syamsuddin; Yudhia Fratidhina; Karningsih Karningsih (International Journal of Health Sciences, 2025)
Stunting remains a persistent public health problem in Indonesia, especially in densely populated urban areas such as East Jakarta. Health cadres serve as community-level communicators who play a strategic role in promoting nutrition awareness and preventive behaviors. Effective interpersonal communication is therefore essential to ensure message uptake among mothers and caregivers. This study aims to explore how community health cadres utilize interpersonal communication to support stunting prevention efforts in East Jakarta, and to identify the communication strategies, challenges, and enabling factors that influence the effectiveness of their role in promoting child nutrition and health behaviors. The research used is qualitative research. The method of data collection used is data A qualitative study was conducted using a thematic analysis approach. In-depth, semi-structured interviews were carried out with 10 active health cadres selected purposively based on experience and involvement in stunting prevention programs. Data were analyzed using Braun and Clarke’s six-phase thematic analysis to generate meaningful patterns and themes. Four major themes emerged: 1.Message simplification and contextualization, enabling improved comprehension among families; 2 Empathy and trust-building, which enhance openness and strengthen rapport; 3 Consistency and continuous mentoring, contributing to sustained behavior change; and 4 Challenges in communication, including limited training, workload burden, and community resistance. These themes collectively demonstrate that interpersonal communication is both relational and context dependent. The study highlights that the effectiveness of health cadres in stunting prevention is strongly influenced by interpersonal communication competencies. Strengthening training, supervision, and institutional support is crucial to enhancing communication quality and optimizing community-based stunting prevention efforts.